Investigating the Process of Urban Physical Development with Emphasis on Real Estate Taxes (Case Study: Five regions of Zahedan) - Abdolali Puor Keikhaei; Mahmoud Reza Anvari; Gholam Reza Miri (تحقیقات کاربردی علوم جغرافیایی)
The physical development of a city will cause growth in other areas. Undoubtedly, the physical development of a country is an important factor in creating the dynamism of the economic system and even the well-being of its people. In this regard, Local governments need the variable, stable and sustainable financial resources for their role in this area. One of these sources is "taxes". The impact of tax on urban physical development plays an important role in its economic and social growth. In the meantime, taxes, especially the tax of estates and tenements, are one of the most reliable ways to provide resources for physical development. Therefore, the purpose of this study is to Investigating the Process of Urban Physical Development with Emphasis on Real Estate Taxes (Case Study: Five regions of Zahedan).The current approach to the present research is qualitative and quantitative and the type of research is applied. In this regard, comprehensive studies were conducted on the research indicators in the study area. The Fuzzy Mamdani model is then used to analyze the information. The results of the model function of the ranking of indicators indicate that public health and environment indices are in a desirable condition, Housing indices and quality of access are at a moderate level and educational, commercial, entertainment and recreational indicators are at an unfavorable level. The results of the status of the studied indices in determining the physical development of each of the 5 study areas in Zahedan in the output of the fuzzy inference system in the MATLAB software show that the 5th region with a score of 0.82 and first area with a score of 0.79 have a desirable level. The 4th area with a score of 0.70 has an average level of physical development. As well as the 2nd area with a score of 0.61 and third area with a score of 0.50 have an undesirable physical development.